Changes in in-hospital mortality in the first wave of COVID-19: a multicentre prospective observational cohort study using the WHO Clinical Characterisation Protocol UK - Docherty, AB; Mulholland, RH; Lone, NI; Cheyne, CP; De Angelis, D; Diaz-Ordaz, K; Donegan, C; Drake, TM; Dunning, J; Funk, S; García-Fiñana, M; Girvan, M; et al. (Elsevier, 2021)
Background Mortality rates in hospitalised patients with COVID-19 in the UK appeared to decline during the first wave of the pandemic. We aimed to quantify potential drivers of this change and identify groups of patients who remain at high risk of dying in hospital.